The Effect of Pair Interaction Model On Improving Students’ Speaking Skills at Royal Training Center (RTC) Anjani - Nurpazila Nurpazila; Usuluddin Usuluddin; Siti Ayu Surayya; Ari Prasetya Ningrum (Journal on Education, 2024)
This present study aimed to know the effect of the pair interaction model on improving students’ speaking skills. This study used pre-experimental design. The participants of this study were students of the Royal Training Center (RTC) who had learn English, involving 18 students. The study’s findings demonstrated that students still lack vocabulary and are nervous while speaking in front of the class. After using the pair interaction model, students feel confident to speak. It can be seen that the result of the average scores pre-test and post-test were 50,77 to 58,00. The result of this study shows that the Pair Interaction Model was effective in improving students' speaking ability.